2019
DOI: 10.28933/ijcr-2019-08-1705
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Spontaneous Pneumoperitoneum: When Not to Operate

Abstract: Pneumoperitoneum is often a surgical emergency related to gastrointestinal tract perforation. On rare occasions, free intraperitoneal air can be present without any discernible cause and is considered Idiopathic Spontaneous Pneumoperitoneum (ISP). Deciding which patients with ISP can be managed conservatively would help prevent some patients from undergoing unnecessary surgery. We describe here two cases of successful management of ISP and the review of literature of ISP management for the past 29 years. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, not all pneumoperitoneum require surgical intervention. It has been observed that in some cases, surgeons may face challenges when it comes to accurately diagnosing and determining the appropriate treatment for patients who have spontaneous pneumoperitoneum and have performed exploratory laparotomies [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all pneumoperitoneum require surgical intervention. It has been observed that in some cases, surgeons may face challenges when it comes to accurately diagnosing and determining the appropriate treatment for patients who have spontaneous pneumoperitoneum and have performed exploratory laparotomies [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s history, clinical examination, and laboratory data should be correlated with the CT findings [ 17 ]. Patients with mild symptoms, benign findings on clinical examination, and no laboratory and imaging evidence of sepsis, bowel ischemia, or perforation can be diagnosed to have non-surgical or spontaneous pneumoperitoneum and can be managed conservatively [ 6 , 16 , 18 ]. Conservative treatment can be started with intravenous antibiotic therapy, nasogastric decompression, and bowel rest.…”
Section: Discussionmentioning
confidence: 99%